A Study of the Corporative Portals as a Tool of Explicit Knowledge Externalization in Universities - Gaspar, Marcos Antonio; Donaire, Denis; Santos, Silvio Aparecido dos; Silva, Maria Conceição Melo (Review of Business Management, 2009)
The corporative portals, enabled by Information Technology and Communication tools, provide the integration of heterogeneous data proceeding from internal information systems, which are available for access and sharing of the interested community. They can be considered an important instrument of explicit knowledge evaluation in the organization, once they allow faster and safer information exchanges, enabling a healthful collaborative environment. In the specific case of major Brazilian universities, the corporate portals assume a basic aspect; therefore they offer an enormous variety and amount of information and knowledge, due to the multiplicity of their activities. This study aims to point out important aspects of the explicit knowledge expressed by the searched universities by the analysis of the content offered in their corporative portals. This is an exploratory study made through direct observation of the existing contents in the corporative portals of two public universities as well as three private ones. A comparative analysis of the existing contents in these portals was carried through; it can be useful to evaluate its use as factor of optimization of the generated explicit knowledge in the university. As results, the existence of important differences could be verified in the composition and in the content of the corporative portals of the public universities compared to the private institutions. The main differences are about the kind of services and the destination of the information that have as focus different public-target. It could also be concluded that the searched private universities focus on the processes related to the attendance of the students, the support for the courses as well as the spreading of information to the public interested in joining the institution; whereas the analyzed public universities prioritize more specific information, directed to the dissemination of the research developed internally or with institutional objectives. Key words: Corporative portal. University. Explicit knowledge.